1982
DOI: 10.1055/s-0037-1620542
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Distribution Studies with Radiolabeled 5-Fluorouracil

Abstract: 5-Fluorouracil (5-FU) is an effective anti-tumor drug, which has been used both as a single agent and in combination with other chemotherapeutic agents for the treatment of tumors such as breast and colorectal carcinoma. We synthesized 5-FU with trace amounts of 18F-5-FU and administered the compounds intravenously to 6 cancer patients. The patients were scanned at 2 hr intervals for 12 hrs and their urine collected whenever possible. We also injected 5-FU with the tracer 18F-5-FU, at pharmacological doses, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Furthermore, Young et al used simple basic radiochemical reactions for the radiolabeling of the 5‐FU. The authors have observed greater than 95% radiochemical purity of this radiolabeled complex . Herein, although the chemical modifications on the main molecule (5‐FU), the radiochemical purity of [ 99m Tc]Tc E was found to be greater than 90%.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Furthermore, Young et al used simple basic radiochemical reactions for the radiolabeling of the 5‐FU. The authors have observed greater than 95% radiochemical purity of this radiolabeled complex . Herein, although the chemical modifications on the main molecule (5‐FU), the radiochemical purity of [ 99m Tc]Tc E was found to be greater than 90%.…”
Section: Discussionmentioning
confidence: 54%
“…Generally, ideal pH of a radiopharmaceutical is 7.4 or can vary between pH 2.0 and 9.0. According to the Young et al study, the pH of the reaction medium was found to play unimportant role in the labeling process of 5‐FU . While reaction conditions are keeping constant and the reaction pH is varied from pH 5.0 to 7.4, no significant differences were observed on labeling efficiency (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is viewed as an "old" drug, it continues being used in a very active manner as part of the treatment of many solid tumors (6)(7)(8). My laboratory has performed for years nuclear imaging with 18 F-5FU and, subsequently, 19 F-MRS studies with that drug (9)(10)(11)(12). The unique advantages of both 18 F for PET and 19 F for MRS have been presented above.…”
mentioning
confidence: 93%